Desain Perencanaan Sequence Penambangan Batubara Short-Term: Short-Term Coal Mining Sequence Planning Design - Razvi, Achmad; Razak, Supardi; Haryono, Ahmad Fauzan (CV Insight Publisher, 2023)
Mine planning activities require analysis to apply the mining sequence to determine the reserve value of the designed mining sequence by considering the ultimate pit limit to match the targeted reserve and economic value. The designed pit limit will be divided into smaller units that consider the recommended stripping ratio value from the company. In the study, 2 PC-800 tools were selected with a month's production value of 274,176 Bcm for overburden excavation and 1 PC-200 with a month's production value of 42 Bcm. 1 PC-200 with a production value for a month of 42,389.57 tonnes for coal excavation. coal excavation, then volume calculations were carried out using the block model method. The results of overburden volume from this study in mining sequence 1, 2, 3, 4. mining sequence 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, and 12 respectivel are (274,093; 274,129; 273,997; 273,754; 273,649; 274,138; 273,710; 274,176; 274,142; 274,176; 274,176; 274,043) Bcm. For the results of coal volume in mining sequences 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, and 12 are (785.2; 17,420; 41,873; 41,684.5; 26,299; 34,938.8; 41,967.9; 42,389.1; 42,389.1; 42,217.5; 42,387.8; 42,389.1) tonnes respectively.